2021
DOI: 10.1021/acssuschemeng.1c05469
|View full text |Cite
|
Sign up to set email alerts
|

Tolerant Bimetallic Macrocyclic [OSSO]-Type Zinc Complexes for Efficient CO2 Fixation into Cyclic Carbonates

Abstract: A new type of sustainable bimetallic zinc complexes bearing macrocyclic thioetherphenolate [OSSO]-type ligands has been developed and employed toward the chemical fixation of carbon dioxide into cyclic carbonates. The effects of reaction variables such as temperature, time, pressure, and molar ratio of epoxide to catalyst on the catalytic performance were systematically investigated. Based on the observations from structural and spectroscopic analyses, a plausible catalytic mechanism for the present reaction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…19 Furthermore, metal complexes with bimetallic architectures facilitate the cooperation between two metal centers under certain circumstances, which has been proven to be one of the attractive strategies in improving their activities in mediating organic transformations 22 and polymerizations. 9,23,24 More recently, we revealed that air-stable dinuclear zinc complexes supported by the macrocyclic thioetherphenolate [OSSO] ligand (Di-[OSSO] ZnX) demonstrated high efficiency toward the coupling reaction of epoxides and carbon dioxide, 25 where the activated epoxide reacts with the nucleophilic cocatalyst to generate real active species of metal-alcoholate (Zn-OR) intermediates under the [OSSO]-type di-zinc complex/TBAB binary catalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…19 Furthermore, metal complexes with bimetallic architectures facilitate the cooperation between two metal centers under certain circumstances, which has been proven to be one of the attractive strategies in improving their activities in mediating organic transformations 22 and polymerizations. 9,23,24 More recently, we revealed that air-stable dinuclear zinc complexes supported by the macrocyclic thioetherphenolate [OSSO] ligand (Di-[OSSO] ZnX) demonstrated high efficiency toward the coupling reaction of epoxides and carbon dioxide, 25 where the activated epoxide reacts with the nucleophilic cocatalyst to generate real active species of metal-alcoholate (Zn-OR) intermediates under the [OSSO]-type di-zinc complex/TBAB binary catalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…A cyclic ligand, designed combining the successful example of the Robson-type ligand employed in the CO 2 /epoxide reactions with various metal centers by Williams and coworkers, [59][60][61][62] with the beneficial role played by the soft sulfur atom in the ligand design for the CO 2 /epoxides coupling, [63] was reported by He and coworkers (Figure 14). [64] In particular they reported that the bimetallic complexes 50-53 activated by TBAB displayed higher activity (TOF up to 4188 h À 1 for the complex 52) in the conversion of PO to PC compared to the corresponding mononuclear complex 53 (TOF = 1392 h À 1 ) under the same reaction conditions (3 MPa; 130 °C, 1 h).…”
Section: Macroyclic Ligandsmentioning
confidence: 98%
“…A large number of catalysts have been developed to catalyse the cycloaddition reaction, including transition metals (e.g., Cr, [15][16][17] Fe, [18][19][20][21] Co, [22][23][24][25][26][27] and Zn [28][29][30][31][32][33] ), main group metals (e.g., Mg, [34][35][36] Al, [37][38][39][40][41][42] Ca [43][44][45][46] ), rare-earth metal catalysts [47][48][49][50][51][52][53][54][55][56][57] and organocatalysts. 5,[58][59][60][61][62][63]…”
Section: Introductionmentioning
confidence: 99%
“…A large number of catalysts have been developed to catalyse the cycloaddition reaction, including transition metals ( e.g. , Cr, 15–17 Fe, 18–21 Co, 22–27 and Zn 28–33 ), main group metals ( e.g. , Mg, 34–36 Al, 37–42 Ca 43–46 ), rare-earth metal catalysts 47–57 and organocatalysts.…”
Section: Introductionmentioning
confidence: 99%